ANALISIS KECELAKAAN KERJA PADA STRUKTUR BAWAH BLENDING SILO PROYEK “EPC TALAVERA” TUBAN MENGGUNAKAN METODE BOWTIE - Bhayangkara, Anugraha Hari; Setyawan, Ary; Handayani, Fajar Sri (Jurnal Riset Rekayasa Sipil, 2023)
The "EPC Talavera" Tuban Project is one of the major projects located in Tuban. Given that the construction of the Blending Silo is being built at a considerable height and certainly requires a large foundation structure, the construction of the Blending Silo carries a relatively high risk of workplace accidents. The purpose of this research is to identify workplace accident risks and evaluate the causes, impacts, and risk responses to accidents during the construction of the substructure of the Blending Silo in the "EPC Talavera" project. To determine the dominant workplace accident risks, risk assessment is performed using probability and severity calculations based on the Risk Management Standard AS/NZ 4360:1999, resulting in an Importance Index value. The method used to evaluate the causes, impacts, and risk responses to workplace accidents is the Bowtie Analysis Method. The results of this research indicate that the most dominant workplace accident risks are the risk of workers being pierced by sharp equipment, the risk of fingers getting caught in the bar bender machine, and the risk of workers being shocked/electrocuted by electrical currents. Based on the bowtie method, the most dominant causes of workplace accidents are scattered sharp equipment, careless/inattentive/unhealthy workers, inadequate equipment, poor bar bender machine conditions, bar bender machine operating methods, exposed welding tool cables, rainy/extreme weather conditions, and electrical current leaks in welding tool bodies. The most dominant impacts of workplace accidents are minor injuries, serious injuries/death, fires, and damage to the bar bender machine. Using the bowtie method, risk responses or controls for the most dominant workplace accident risks are also analyzed, along with an analysis of escalation factors and their controls.